M.V. Lomonosov's world view. In honor of Great Russian scientist's 300th anniversary - M. A. Maslin; О. А. Volnyakova (Тонкие химические технологии, 2011)
Fundamental factors of the formation of scientific and philosophical world view of the great Russian scientist and thinker M.V. Lomonosov (1711-1765) are exposed. Correlation between scientific and philosophical reasoning in his creation work is analysed. His contribution to developing the national philosophy is shown.